An assessment of the value of an African landscape. The case of the Mara Basin, Kenya. (October 2018) - Kiptala, Jeremiah K.; Hessels, Tim; Laa, Barbara; van der Zaag, Pieter
Abstract: Ecosystems provide social, ecological and economic benefits and are linked through the landscape. Landscape degradation and loss of biodiversity undermine ecosystem functioning especially in vital ecosystems such as the Mara Basin in Africa. Holistically monitored and assessed landscape provide values to support conservation strategy which could enhance sustainable resource utilisation. The study relied on high resolution 10-m Sentinel 2A, Landsat 30-m and SEBAL to generate biophysical parameters for valuation in the landscapes. A household survey was used to derive forest benefits to local livelihoods. The well conserved Trans Mara forest provided high ecological benefits but few social benefits to the local community. Tea buffers have proven to be an effective conservancy strategy for the forest ecosystem. The long term carbon-based benefits in conservation areas of rural Africa is hindered by communities' high dependency on firewood and charcoal energy. The land policy on limited livestock access to the pastoralists in the conservancies should be based on the livestock carrying capacity of the lands. Further, the valuation maps can be used for land use planning where critical wildlife protection areas, movement corridors and mixed use zones of high livestock value can be identified. The holistic assessment of value of African landscape based on key functionalities and linked spatially over the landscape using remotely sensed data is indeed crucial to improve decision making and conservation strategy towards sustainable ecosystem management. Highlights: Conservation buffers provide sustainable protection to vital landscape ecosystems. Ecological ecosystem values should be balanced with social and economic benefits. Carbon-based benefits cannot be sustained with current energy uses in rural Africa. Holistic assessment of landscape values can aid land use and conservation policy.